New Epoxy sugar based glucose derivatives as eco friendly corrosion inhibitors for the carbon steel in 1.0 M HCl: Experimental and theoretical investigations - Rbaa, M.; Dohare, P.; Berisha, A.; Dagdag, O.; Lakhrissi, L.; Galai, M.; Lakhrissi, B.; Touhami, M. Ebn; Warad, I.; Zarrouk, A. (Journal of alloys and compounds, 2020)
In this study, we chose to synthesize new sugar based glucose derivatives as ecological corrosion inhibitors for carbon steel in acidic medium. The products obtained in the form of syrupy liquids, and the purity of obtained compounds was characterized by NMR spectroscopy analysis. The corrosion inhibition activities for both compounds were evaluated by electrochemical and rheological methods. Thus, the results of the experimental tests have been confirmed by theoretical studies (DFT, MC and MD simulations). The surface study of carbon steel has been characterized by the scanning electron spectroscopy (SEM). The gravimetric solutions were identified using UV-Vis spectroscopy and Inductively Coupled Plasma-Optical Spectroscopy (ICP-OES). •Newly both glucose derivatives was synthesized and evaluated as corrosion inhibitor for steel in acidic medium.•Adsorption of G-C12 and G-C6, obeyed the Langmuir adsorption isotherm model their adsorption was supported by SEM and UV-vis spectroscopic analyses.•The experimental results were correlated with DFT and MC stimulation results.